Loading Frequency Effects on Concrete Fatigued in Compression - Dolara, E. (Engineering Transactions, 1997)
This papers reports the experimental results of tests performed on prismatic concrete specimens in compression. The specimens have been subjected to a large amount of fatigue cycles (High Cycle Fatigue, HCF). lt is common opinion that, in the case of plain concrete in compression, fatigue does not depend on the loading frequency. On the contrary, the performed tests show that: a) the energy dissipation in the material depends on the loading frequency; b) the more fatigued is the material, the less its behaviour depends on the loading frequency.